Pollution: Incompatibilities between the legal and technical concepts - Cerri Neto, Mauro [UNESP]; Ferreira, Gilda Carneiro [UNESP] (My University, 2009)
This paper presents the method, procedures and results obtained through the comparison between legal and technical of pollution terms. The purpose was to show if the correct or wrong forms wrote these concepts and to check any incompatibilities between them. Different sources were consulted for selection of the concepts, such as books, papers, laws, judicial decisions, dictionaries, glossaries, electronic medias, internet. The scientific method used in this research was the comparative technics. It was constituted by the essential concept of pollution, since the essential, primary, necessary, universal, to general and common. The comparison permitted to reach three possibilities of classification: 1. literal reproduction of the legal concept; 2. the essence of the technical concept is in accordance with the essence of the legal concept; 3. the essence of the technical concept is not in accordance with the legal concept (with appropriate justifications). The results of the research show several incompatibilities between the legal and technical concepts.
Poluição: Incompatibilidades entre conceitos legal e técnico
Keywords: Environmental pollution; Legal concept; Pollution; Technical concept